Enhancing Stability of Boesenbergia rotunda Bioactive Compounds: Microencapsulation via Spray-Drying and Its Physicochemical Evaluation - Fahmi Ilman Fahrudin; Suphat Phongthai; Pilairuk Intipunya (Foods)
This study aimed to microencapsulate Boesenbergia rotunda (fingerroot) extract using maltodextrin (MD) and gum arabic (GA) as wall materials via spray-drying to improve powder physicochemical properties and protect bioactive compounds. MD and GA were employed as wall materials in varying ratios (MD:GA of 1:0, 0:1, 1:1, 2:1, 1:2) to evaluate their effects on the physicochemical properties of the resulting microcapsules. Spray-dried microcapsules were evaluated for morphology, flowability, particle size distribution, moisture content, hygroscopicity, solubility, encapsulation efficiency, major bioactive compound retention, and thermal stability. The extract encapsulation using MD:GA at 1:1 ratio (MD1GA1) demonstrated a favorable balance, with high solubility (98.70%), low moisture content (8.69%), low hygroscopicity (5.08%), and uniform particle morphology, despite its moderate EE (75.06%). SEM images revealed spherical particles with fewer surface indentations in MD-rich formulations. Microencapsulation effectively retained pinostrobin and pinocembrin in all formulations with pinostrobin consistently retained at a higher value, indicating its higher stability. The balanced profile of physical and functional properties of fingerroot extract with MD1GA1 microcapsule makes it a promising candidate for food and nutraceutical applications.